Better judgment: how three judges are bringing justice back to the courts - Holding, Reynolds (University of California Press, 2025)
"The book is about three remarkable judges whose compelling and diverse lives tell the story of how the federal courts have over decades been losing the power to deliver justice-and how they can get it back. It brings readers into the little-known but fascinating world of the courts' true workhorses, federal trial judges, who handle the vast majority of cases and have rarely, if ever, been written about. It also makes the controversial case that judges are good for democracy and should have more power, not less, as so many other people have argued"--